FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN METODE KONTRASEPSI EFEKTIF TERPILIH (MKET) PADA PUS DI PUSKESMAS MARGOREJO KOTA METRO - Herlina, Herlina; M. Ridwan; Firda Fibrila (JOEL: Journal of Educational and Language Research, 2022)
The rate of population growth per year is a figure that shows the average rate of population growth per year over a period of time. So that the rate of Population Growth per Year during 2010-2020 averaged 1.25 percent, slowing down compared to the 2000-2010 period of 1.49 percent and reaching 1.17 percent in 2022, one of the causes was the government's policy to suppress the rate of population growth through the Family Planning program launched in 1980. The use of MKET is strongly influenced by factors that influence the choice of contraceptive methods used, namely preposition factors (age, education, number of children, knowledge, attitudes) supporting factors (availability of contraceptives, distance from home to puskesmas, travel time and cost) driving factors such as support for health workers. The results showed that there was a relationship between knowledge, attitudes, husband support and the role of health workers in the use of MKET contraceptives. The health promotion program that has been carried out needs to be improved both in the quantity / number of activities and the quality of IEC (Communication, Information and Education), especially to PUS in the use of MKET contraceptives. Assistance is needed and actively involves the role of the husband when making decisions on the selection of contraceptives as he wants.